Exploring germination thresholds and seed properties of Ambrosia artemisiifolia populations from different European regions for improving control strategies - Nikolić, Nebojša; Šoštarčić, Valentina; Šćepanović, Maja; Masin, Roberta (Frontiers in Agronomy, 2025)
IntroductionAmbrosia artemisiifolia, a highly invasive weed species, poses significant challenges to agriculture and human health. This study investigated the germination thresholds and physical properties of A. artemisiifolia populations from diverse regions in Europe, encompassing Serbia, Croatia, Italy, and France.ResultsResults revealed intriguing variations in germination thresholds among the populations. The Italian population exhibited the lowest base temperature (Tb) of 0.58°C, closely followed by the Croatian population (1.49°C), statistically similar to the Serbian (1.46°C) and French (2.74°C) populations. In contrast, the Serbian population displayed the lowest base water potential (Ψb) of −1.44 MPa, followed by the French population (−1.23 MPa), with no significant differences observed between the Italian (−0.78 MPa) and Croatian (−0.80 MPa) populations. Analysis of physical seed properties unveiled notable disparities in size, weight, and shape. The Italian population boasted the smallest, lightest, and most spherical seeds, while the French population harbored the largest and most elongated seeds. Interestingly, the seeds of the Croatian population were the heaviest.ConclusionsThis study underscores the adaptability of A. artemisiifolia populations to diverse climatic conditions, showcasing varied responses across regions. These findings elucidate the intricate interplay between environmental factors and seed traits, offering valuable insights for the development of effective weed management strategies.